2022
DOI: 10.1038/s41467-022-31585-w
|View full text |Cite
|
Sign up to set email alerts
|

Structures of LIG1 that engage with mutagenic mismatches inserted by polβ in base excision repair

Abstract: DNA ligase I (LIG1) catalyzes the ligation of the nick repair intermediate after gap filling by DNA polymerase (pol) β during downstream steps of the base excision repair (BER) pathway. However, how LIG1 discriminates against the mutagenic 3′-mismatches incorporated by polβ at atomic resolution remains undefined. Here, we determine the X-ray structures of LIG1/nick DNA complexes with G:T and A:C mismatches and uncover the ligase strategies that favor or deter the ligation of base substitution errors. Our struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(68 citation statements)
references
References 80 publications
6
61
1
Order By: Relevance
“…Our previous and present LIG1 structures revealed the features of DNA substrate and LIG1 interaction that dictate accurate versus mutagenic outcomes (53). Our structures contribute to the understanding of the mechanism by which LIG1 discriminates against non-canonical DNA intermediates during nick sealing at each individual step of the ligation reaction as well as how the ligase active site engages with nick DNA distinctly depending on the architecture of cognate (step 2), mismatched (step 1 or 2), or ribonucleotide (step 3)-containing ends (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Our previous and present LIG1 structures revealed the features of DNA substrate and LIG1 interaction that dictate accurate versus mutagenic outcomes (53). Our structures contribute to the understanding of the mechanism by which LIG1 discriminates against non-canonical DNA intermediates during nick sealing at each individual step of the ligation reaction as well as how the ligase active site engages with nick DNA distinctly depending on the architecture of cognate (step 2), mismatched (step 1 or 2), or ribonucleotide (step 3)-containing ends (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 71%
“…In our previously solved LIG1/A:T structure, we reported that the active site can accommodate a cognate A:T base pair where DNA-AMP intermediate is formed (53). The comparison of the 2Fc-Fo maps at 3’-OH and 5’-P ends of the nick DNA demonstrated continuous and discontinuous maps in the LIG1 structures of rG:C and A:T, respectively (Figure 2A-B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations